2020
DOI: 10.1177/1526924820913503
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Application for Communication Increases the Efficiency of Organ Procurement and Transplantation

Abstract: Background: Donor organ recovery is a complex process involving organ procurement organizations and multiple surgical teams from various transplant centers. Nearly 30% of discarded organs are wasted due to reasons related to improper coordination and communication. Problem Statement: Lack of real-time communication results in many hours of preventable delay between procurement and transplant teams resulting in the high volume of organ waste, clinical frustration, and critical delays. Methods: A Plan-Do-Study-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…9 The application was used by doctors and surgeons, transplant coordinators, procurement coordinators, HLA typists, and other supporting staff and provided team-based messaging, read receipts, the ability to send photos and videos, customized notifications, HIPAA compliance, administrative user management, external messaging capabilities, and audit reporting/documentation. 9 Users reported that the application increased their clinical productivity and awareness of case progress, and reduced redundant phone calls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 The application was used by doctors and surgeons, transplant coordinators, procurement coordinators, HLA typists, and other supporting staff and provided team-based messaging, read receipts, the ability to send photos and videos, customized notifications, HIPAA compliance, administrative user management, external messaging capabilities, and audit reporting/documentation. 9 Users reported that the application increased their clinical productivity and awareness of case progress, and reduced redundant phone calls.…”
Section: Discussionmentioning
confidence: 99%
“…While the impact on time spent by personnel evaluating and communicating about organ offers was not reported, the quality improvement process of developing and implementing the application was followed by a decrease in the time from initial offer to transplant (from 16 to 21 h previously to 10 h with use of the application) and by a 35% increase in the number of kidney transplants performed. 9 Improving the efficiency of the offer process is important for increasing the utilization of donated organs by offering them to centers that are likely to accept them and to avoid increasing the workload placed on organ transplant personnel reviewing the offers beyond a sustainable level. When the increase in the volume of offers received is not accompanied by a corresponding increase in organs transplanted at the center, as we observed in this study, there is no additional reimbursement to support hiring additional personnel to manage those offers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients and their relatives will now be able to prepare themselves properly for the procedure with facts about anticipated prices, nearby organ banks, and other important data. Given the various criteria regulating organ donation, such as blood group and form of antigen, the software uses Azure Machine Learning to determine an organ match and approximate the rank and time needed for an expecting recipient (Pahl et al 2020). If a potential donor has an injury or passes away, there is no convenient way to search the records to efficiently preserve the organs.…”
Section: Organ Transplantationmentioning
confidence: 99%